Development and Current Status of Full-scale Anaerobic Digestion Plants for Organic Fraction of Municipal Solid Waste in Türkiye - Ahmet Musluoğlu; Serra Selin Övez; Recep Kaan Dereli; Kadriye Elif Maçin; Kadir Özçelik; Muhammad Waqas; Osman Atilla Arıkan (BioEnergy Research, 2026)

Simulation and Optimization of H2, CO, CO2, and CH4 Obtained from the Co-pyrolysis of Date Seeds and Tire Plastic Waste - Lisandra Rocha-Meneses; Muhammad Shahbaz; Abrar Inayat; Mario Luna-delRisco (BioEnergy Research, 2025)

An Exploration of Strategies for Conducting Kinetic Analysis of Lignocellulosic and Algal Biomass Pyrolysis - Vikul Vasudev; Xiaoke Ku; Shri Ram; Tarique Ahmed Memon; Yogesh Patil; Muhammad Shoaib; Zhiwei Liu; Zishuo Wang (BioEnergy Research, 2025)

Conversion of Agricultural Waste into High-Rank Solid Fuel Through Sequential Wet and Dry Torrefaction Processes - Muhammad Ade Andriansyah Efendi; Toto Hardianto; Pandji Prawisudha; Firman Bagja Juangsa (BioEnergy Research, 2025)

Understanding the Thermal and Physical Properties of Biochar Derived from Pre-washed Arabica Coffee Agroindustry Residues - Adi Setiawan; Siti Nurjannah; Shafira Riskina; Zahra Fona; Muhammad; Matthew Drewery; Eric M. Kennedy; Michael Stockenhuber (BioEnergy Research, 2025)

Enhancing Surface Properties of Circular Carbon Biochar Derived from Spent Coffee Beans Through ZnCl2/KOH Activation - Gowthami D.; R. K. Sharma; M. Khalid; Muhammad Yusri Ismail (BioEnergy Research, 2024)

Waste Palm Leaves-Based Hydrochar Support Catalytic Esterification of Palm Fatty Acid Distillate - Muhammad Aliyu; Umer Rashid; Wan Azlina Wan Ab Karim Ghani; Mohamad Amran Mohd Salleh; Balkis Hazmi; Fahad A. Alharthi; Elsa Antunes; Jianglong Yu (BioEnergy Research, 2024)

Solid-State Fermentation as a Green Technology for Biomass Valorization: Optimization Techniques for Bioprocess—An Overview - Luiz Henrique Sales de Menezes; Polyany Cabral Oliveira; Eliezer Luz do Espírito Santo; Márcia Soares Gonçalves; Muhammad Bilal; Héctor A. Ruiz; Erik Galvão Paranhos da Silva; Luiz Carlos Salay; Julieta Rangel de Oliveira; Marcelo Franco (BioEnergy Research, 2023)

Transforming Lignin Biomass to Value: Interplay Between Ligninolytic Enzymes and Lignocellulose Depolymerization - Namra Ahmad; Shakira Aslam; Nazim Hussain; Muhammad Bilal; Hafiz M. N. Iqbal (BioEnergy Research, 2023)
Lignin is the main constituent of lignocellulosic biomasses, which have a significant untapped ability to replace ecologically unfavorable and non-renewable fossil fuels. The lignin is broken down by ligninolytic bacteria, which also use a peripheral pathway to transform heterogeneous lignin derivatives into central intermediates like protocatechuate or catechol. By undergoing ring cleavage through the -ketoadipate pathway, these intermediates become metabolites by producing acetyl-CoA for internal product biosynthesis, including the creation of triacylglycerols and polyhydroxyalkanoates. Expanding our understanding of ligninolytic microbial communities, strains, and enzymes through bioprospecting can help us better understand the metabolism of aromatics. The most viable idea for sustainable development is the valorization of lignin into biopolymers as well as other high-value goods. This process is now being used to generate a variety of biopolymers, including polyesters, epoxies, phenol resins, poly (lactic acids), poly hydroxyl alkanoates, and polyurethanes. Furthermore, lignin recalcitrance remained a possible barrier to efficient lignin valorization, prompting several efforts to design high-efficiency bioprocesses to produce specific polymer types as well as other important bioproducts. Graphical Abstract

The Application of Chemometric Methods in the Production of Enzymes Through Solid State Fermentation Uses the Artificial Neural Network—a Review - Luiz Henrique Sales de Menezes; Adriana Bispo Pimentel; Polyany Cabral Oliveira; Iasnaia Maria de Carvalho Tavares; Héctor A. Ruiz; Murammad Irfan; Muhammad Bilal; Thiago Pereira das Chagas; Erik Galvão Paranhos da Silva; Luiz Carlos Salay; Julieta Rangel de Oliveira; Marcelo Franco (BioEnergy Research, 2023)

Biogas Production Through Mono- and Co-digestion of Pineapple Waste and Cow Dung at Different Substrate Ratios - Adila Fazliyana Aili Hamzah; Muhammad Hazwan Hamzah; Hasfalina Che Man; Nur Syakina Jamali; Shamsul Izhar Siajam; Pau Loke Show (BioEnergy Research, 2022)

Anaerobic Digestion of Digested Manure Fibers: Influence of Thermal and Alkaline Thermal Pretreatment on the Biogas Yield - Muhammad Usman Khan; Birgitte K. Ahring (BioEnergy Research, 2021)

Sustainability of Palm Biodiesel in Transportation: a Review on Biofuel Standard, Policy and International Collaboration Between Malaysia and Colombia - Mohd Nur Ashraf Mohd Yusoff; Nurin Wahidah Mohd Zulkifli; Nazatul Liana Sukiman; Ong Hwai Chyuan; Masjuki Haji Hassan; Muhammad Harith Hasnul; Muhammad Syahir Amzar Zulkifli; Muhammad Mujtaba Abbas; Muhammad Zulfattah Zakaria (BioEnergy Research, 2021)

Simplex-Centroid Design and Artificial Neural Network-Genetic Algorithm for the Optimization of Exoglucanase Production by Penicillium Roqueforti ATCC 10110 Through Solid-State Fermentation Using a Blend of Agroindustrial Wastes - Nájila da Silva Nunes; Lucas Lima Carneiro; Luiz Henrique Sales de Menezes; Marise Silva de Carvalho; Adriana Bispo Pimentel; Tatielle Pereira Silva; Clissiane Soares Viana Pacheco; Iasnaia Maria de Carvalho Tavares; Pedro Henrique Santos; Thiago Pereira das Chagas; Erik Galvão Paranhos da Silva; Julieta Rangel de Oliveira; et al. (BioEnergy Research, 2020)

Screening of Lipase-Producing Bacteria and Optimization of Lipase-Mediated Biodiesel Production from Jatropha curcas Seed Oil Using Whole Cell Approach - Abdul Haq; Sana Adeel; Alam Khan; Qurrat ul ain Rana; Muhammad Adil Nawaz Khan; Muhammad Rafiq; Muhammad Ishfaq; Samiullah Khan; Aamer Ali Shah; Fariha Hasan; Safia Ahmed; Malik Badshah (BioEnergy Research, 2020)

Microalgae Isolation for Nutrient Removal Assessment and Biodiesel Production - Muhammad Arif; Le Wang; El-Sayed Salama; Mian Sabir Hussain; Xiangkai Li; Mohammed Jalalah; M. S. Al-Assiri; Farid A. Harraz; Min-Kyu Ji; Pu Liu (BioEnergy Research, 2020)

Thermogravimetric Kinetics of Catalytic and Non-Catalytic Pyrolytic Conversion of Palm Kernel Shell with Acid-Treated Coal Bottom Ash - David Onoja Patrick; Suzana Yusup; Noridah B. Osman; Haslinda Zabiri; Yoshimitsu Uemura; Muhammad Shahbaz (BioEnergy Research, 2020)

Enhanced Lipid Recovery from Marine Chlorella Sp. by Ultrasonication with an Integrated Process Approach for Wet and Dry Biomass - Muhammad Amin; Pakamas Chetpattananondh (BioEnergy Research, 2019)

Directed Evolution of Clostridium phytofermentans Glycoside Hydrolase Family 9 Endoglucanase for Enhanced Specific Activity on Solid Cellulosic Substrate - Sajjad Ahmad; Hui Ma; Muhammad Waheed Akhtar; Yi-Heng Percival Zhang; Xiao-Zhou Zhang (BioEnergy Research, 2014)